2009
DOI: 10.1089/apc.2008.0249
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Anal Sex: Sexual Practices Associated with HIV Risk Reduction among Men Who Have Sex with Men in Boston, Massachusetts

Abstract: Men who have sex with men (MSM) continue to bear a disproportionate HIV and sexually transmitted disease (STD) burden. The current study examined the frequency and associations of sexual risk reduction behaviors among a sample of MSM in the greater Boston, Massachusetts area. One hundred eighty-nine MSM completed a one-time behavioral and psychosocial assessment between March 2006 and May 2007. Logistic regression procedures examined the association of demographic, psychosocial, and behavioral factors with ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 27 publications
6
34
0
Order By: Relevance
“…Sex toys are often used by MSM during solo and partnered sexual activities to enhance the sexual experience 18. Seen as a way to reduce HIV risk acquisition by many MSM,19 sex toy use has been described in the past as a risk factor for hepatitis C,20 lymphogranuloma venereum proctitis21 and HIV22 infections. To our knowledge, this is the first study identifying use of anal sex toys as a risk factor for syphilis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Sex toys are often used by MSM during solo and partnered sexual activities to enhance the sexual experience 18. Seen as a way to reduce HIV risk acquisition by many MSM,19 sex toy use has been described in the past as a risk factor for hepatitis C,20 lymphogranuloma venereum proctitis21 and HIV22 infections. To our knowledge, this is the first study identifying use of anal sex toys as a risk factor for syphilis infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in their sample of African American MSM, Mimiaga and colleagues (2010) reported that experiencing more clinically-significant symptoms of depression was associated with more stimulant use during sex. Other work published by members of that same research team showed that depression was associated with a nearly tripled risk of having unprotected anal sex with a serodiscordant partner, as well as an eight-fold increase in the likelihood of recently having had a sexually transmitted infection (Reisner et al ., 2009a). Additionally, MSM who were trying to reduce their risk for HIV by engaging in specific low-risk activities were less likely to experience depression than men who were not engaging in these specific risk-reduction practices (Reisner et al ., 2009b).…”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6][7] Evidence from studies has shown that condom use among MSM remains at a very low level. 8 It has been broadly reported in China that most MSM had sex with casual sexual partners and never used a condom. 9,10 In many countries, MSM behaviors are highly unacceptable, and there is strong social pressure against the behavior of MSM.…”
Section: Introductionmentioning
confidence: 99%